An analysis on the effectiveness of elected officials and council management towards improving service delivery and development of towns. a case study of Shurugwi town council from 2013-2017 - Paradza, Natasha (Midlands State University, 2018)
Public service delivery is essential to citizens worldwide. Service delivery therefore is providing basic needs which are essential in life such as housing, water supply, waste management, sewerage reticulation and treatment and if residents are denied those basic needs the environment becomes unfriendly and they are subjected to a lot of discomfort and prone to diseases. However, looking at the Zimbabwean context due to economic instability and financial constraints it has crippled the Local Authorities leading to poor service delivery. If residents fail to receive effective and efficient services it results in frustrations and the blame is pinned at the council officials. Therefore, the aim of this study is to analyse the effectiveness of elected officials and council management towards improving service delivery in Shurugwi. To come up with a sound thesis, four specific objectives with their underlying hypothesis were designed and assessed by quantitative and qualitative research design. To add on, the research was a case study approach thus the researcher greatly employed primary and secondary sources of data and made use of articles, books, interviews and questionnaires. Background information such as theoretical, conceptual frameworks were established together with literature review. After doing the research, the researcher concluded that there should be effective communication between the residents and council officials through the aid of elected officials who represent the interests of the grassroots.